Effect of Long-term Administration of Cordycepin from Cordyceps militaris on Testicular Function in Middle-aged Rats - Sohn, Sang-Hyun; Lee, Su-Chan; Hwang, Seock-Yeon; Kim, Sung-Won; Kim, Il-Woung; Ye, Michael B.; Kim, Si-Kwan (Planta Medica, 2012)
This study was carried out to examine the potential beneficial effect of cordycepin on the decline of testicular function induced with age. A total of 30 male Sprague-Dawley rats (twenty-four 12-month-olds and six 2-month-olds) were divided into five groups. The young control (YC) and middle-aged control (MC) groups received vehicle only. Cordycepin-treated groups were administered daily doses of oral cordycepin at 5, 10, and 20 mg/kg body weight for 4 months. As a result, the MC group exhibited epididymal weight loss, decreased sperm motility, and reduced spermatogenesis compared to the young control group. Interestingly, the epididymal weights of middle-aged rats were dose-dependently increased by treatment with cordycepin. Cordycepin also improved calcium levels and decreased urea and nitrogen, uric acid, and creatinine in the blood of middle-aged rats. In addition, cordycepin significantly increased sperm motility and the progressiveness of sperm movement. All cordycepin-treated groups showed well-arranged spermatogonia, densely packed cellular material, and increased numbers of mature spermatozoa in the seminiferous lumen compared to the middle-aged control group. These results indicate that long-term administration of cordycepin can counteract the decline of testicular function in middle-aged rats.
Keywords: cordycepin; Cordyceps militaris; testicular function; sperm motility; spermatogenesis-aging